Bioinformatics analysis and development of functional markers for TaMYB4-1A in wheat - Dan Zhao; Yuru Ma; Yufeng Yang; Zhaoyang Li; Chaoran Wang; Yuhan Fu; Yang Chen; Tengteng Zhang; Yi Ding; Huiqiang Wang; Xuehui Zhang; Hao Zhang (PLoS ONE, 2025)
MYB transcription factors play crucial roles in various stages of plant growth and development. Bioinformatics analysis revealed that wheat TaMYB4-1A contains two conserved MYB domain. The coding region of TaMYB4-1A is 792 bp, encoding 263 amino acids. TaMYB4-1A is a hydrophilic protein, and its encoded protein is localized in the cell nucleus. Evolutionary tree analysis indicates that the TaMYB4 protein shares the closest relationship with Aegilops, barley, and rye. Tissue-specific expression analysis revealed that TaMYB4-1A is expressed in wheat roots, stems, leaves, and seeds 14 days post-flowering, with the highest expression in the seeds. Promoter cis-acting element analysis showed that the promoter region of TaMYB4-1A contains various cis-acting elements, including meristem regulatory elements, drought-induced elements, and hormone response elements. qRT-PCR analysis showed that the expression of TaMYB4-1A is suppressed under high salinity and PEG treatment, suggesting that TaMYB4-1A may play a critical regulatory role in response to salt and drought stress. There are two haplotypes of TaMYB4-1A, namely Hap-1A-I and Hap-1A-II. The average plant height of varieties with haplotype Hap-1A-I is significantly higher than that of varieties with haplotype Hap-1A-II. This research provides a basis for future in-depth investigation of the biological function of the TaMYB4-1A gene and offers promising candidate genes for molecular marker-assisted wheat breeding.